Foundation ActionScript 3 - Milbourne, Paul.; Richardson, Darren; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
ActionScript 3 is a full-fledged programming language, with complete object-oriented capabilities, event handling, sound and video support, drawing capabilities, support for regular expressions, and much more. Whether you are just starting out on the road to computer programming and animation or an experienced developer who wants to learn a new language, you’ll find all you need to know in Foundation ActionScript 3. Starting with the fundamentals, you’ll learn how to add interactivity to your Flash movies by using ActionScript objects, manipulating sound and video, and harnessing the power of regular expressions and XML. The book concludes with two case studies to consolidate what you’ve learned and introduce some additional advanced techniques. You’ll gain a solid understanding of the exciting world of ActionScript 3 and see how everything fits together, so you’ll be able to build your own professional applications. The sensible layout of the book makes it easy to find information about specific techniques. It focuses on the essential skills that will enable you to get up and running quickly. With this book as your guide, you’ll be creating killer Flash applications before you know it.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems